Selective laser trabeculoplasty for the treatment of intraocular pressure elevation after viscocanalostomy with Ologen implant in the management of primary open-angle glaucoma: a retrospective cohort study - Ahmed AM Gad; Bahaa-Eldin Hasan Abdulhalim; Amal F Gharib; Amr Mahfouz Mohammed (BMC Ophthalmology)
Abstract Background Selective laser trabeculoplasty (SLT) is a non-invasive treatment option for glaucoma. It uses a Q-switched Nd: YAG laser. The aim of this study was to evaluate the efficacy of SLT as a treatment option for eyes with primary open-angle glaucoma (POAG) that have previously undergone viscocanalostomy with an Ologen implant, displaying uncontrolled intraocular pressure (IOP). Methods This retrospective cohort study included 26 eyes of 26 patients with POAG who had had SLT after viscocanalostomy or phacoviscocanalostomy with Ologen implant. These eyes showed a progression of glaucomatous damage, the IOP was above 21 mmHg, or with intolerable glaucoma medications. SLT was done using Tango Reflex multimodality YAG/SLT laser which is a Q-switched Nd: YAG laser producing a single 532 nm wavelength pulse with a 400 mm spot size and 3 ns pulse duration. The follow-up period was one year. Results One year post-SLT, complete success was achieved in 19 cases (73.1%), qualified success in 4 cases (15.4%), and failure in 3 cases (11.5%). The mean decrease in IOP was 5.64 ± 4.05 mmHg, the mean reduction of antiglaucoma medications was 1.00 ± 0.85, and the mean percentage of reduction in IOP was 23.5 ± 16.4. There was a statistically significant decrease in IOP and antiglaucoma medications (p = < 0.01). Conclusion SLT is a simple and effective procedure that can be used as a treatment option for eyes with POAG after viscocanalostomy with Ologen implant to reach the target IOP and decrease the number of antiglaucoma medications.